Corporate finance : core principles & applications - Ross, Stephen A.; Westerfield, Randolph; Jaffe, Jeffrey F., 1946-; Jordan, Bradford D.; Shue, Kelly, 1975- (New York: McGraw Hill, 2024)
"Corporate Finance: Core Principles & Applications is rich in valuable learning tools and support to help students succeed in learning the fundamentals of financial management"--
Includes indexes.
Keywords: Corporations -- Finance